The historical writing of the Monography in contemporary Morocco: a contribution to the study of backgrounds, subject and methodology - Abarzak, Elbachir (Journal of Humanities & Social Sciences, 2019)
Form of requirement to rewrite the history of Morocco, end and destined for historical writing since the dawn of contemporary Moroccan independence to today. To achieve this endeavor went searching at first with the pioneers of traditional historical writing about writing encyclopedic local dates for various parts of the country, leaving archival sources and the rich historical material, formed an indispensable starting point for subsequent generations of researchers. Has contributed to those pioneers in founding the transformation of historical research in Morocco beginning in the 1970s, crystallized modern path generated in regional history, formed in some respects a continuation of historical writing traditional regional hand and open to Thematic issues and new methodology.